2010
DOI: 10.1002/ajmg.a.33755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 64 candidate single nucleotide polymorphisms as risk factors for neural tube defects in a large Irish study population

Abstract: Individual studies of the genetics of neural tube defects (NTDs) contain results on a small number of genes in each report. To identify genetic risk factors for NTDs, we evaluated potentially functional single nucleotide polymorphisms (SNPs) that are biologically plausible risk factors for NTDs but that have never been investigated for an association with NTDs, examined SNPs that previously showed no association with NTDs in published studies, and tried to confirm previously reported associations in folate-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 41 publications
0
24
1
1
Order By: Relevance
“…MTHFR plays an important role in the folate metabolism pathway and regulates the intracellular folate pool for synthesis and methylation of DNA folate metabolism [26]. It is investigated that the SNPs of MTHFR gene has a strong association with NTDs [27,28]. Spina bifida is a class of neural tube defects, it is reported that ALDH1L1 rs873696 and MTHFR rs1801133 are not risk factors of spina bifida [11].…”
Section: Discussionmentioning
confidence: 98%
“…MTHFR plays an important role in the folate metabolism pathway and regulates the intracellular folate pool for synthesis and methylation of DNA folate metabolism [26]. It is investigated that the SNPs of MTHFR gene has a strong association with NTDs [27,28]. Spina bifida is a class of neural tube defects, it is reported that ALDH1L1 rs873696 and MTHFR rs1801133 are not risk factors of spina bifida [11].…”
Section: Discussionmentioning
confidence: 98%
“…The geographical distribution of NTDs in Turkey indicates a relationship between the development of NTDs and socioeconomic and environmental factors. Although some polymorphisms leading to genetic effects have been demonstrated in studies worldwide (Botto and Yang, 2000;Pangilinan et al, 2010;Carter et al, 2011), the specific genes and genetic factors involved have yet to be determined. A 677C→T mutation in the methylenetetrahydrofolate reductase gene, which is thought to cause NTDs, is not a risk factor in the Turkish population (Boduroğlu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although Nanog3 upregulation is observed in 48%, Oct4 and Sox2 in 40% of the patients, the differences were not significant, only null mutation was significantly correlated with NTD (Saxena et al, 2013). The most common maternal risk factors associated with NTDs in infants include folic acid deficiency, overweight, diabetes, drugs, consanguinity, and single-nucleotide polymorphisms (Kondo et al, 2009;Herrmann and Obeid, 2011;Carter et al, 2011). The prevalence of NTDs at birth varies significantly by national geographical strata, ethnicity, and racial groups.…”
Section: Introductionmentioning
confidence: 95%
“…Brachyury mutants) have defective mesoderm formation and abnormal axial development (Stott et al, 1993), and several studies have identified an association between a common variant in T (i.e. TIVS7-2, rs3127334) and the risk of neural tube defects in humans (Carter et al, 2011; Jensen et al, 2004; Morrison et al, 1996; Morrison et al, 1998; Shields et al, 2000). …”
Section: Introductionmentioning
confidence: 99%